Time Management Towards Successful Entrepreneurship - Mellasanti Ayuwardani; Sri Eka Sadriatwati; Rara Ririn Budi Utaminingtyas; Rustono, Rustono; Irin Mirrah Luthfia (Cita konsultindo, 2025)
In the era of Industry 5.0, the utilization of technology in economic growth is no longer unfamiliar. This has given rise to many new entrepreneurs and consumerist behaviors, including among university students. The Business Administration Department of Semarang State Polytechnic, where students acquire various business knowledge, is no exception. Many students run businesses while actively pursuing their studies. This study involved 34 respondents who were active undergraduate students in the Business Administration Department and engaged in entrepreneurship. The research results obtained a calculated t-value for time management (3.176) > t-table (1.694) with a significance value of 0.003 < 0.05 for business growth. Therefore, it can be concluded that time management has a positive and significant influence on the growth of businesses run by undergraduate entrepreneurs in the Business Administration Department of Semarang State Polytechnic. The adjusted R-squared value of 0.216 indicates that 21.6% of business growth is influenced by time management. Based on these findings, it can be concluded that to advance their businesses, active undergraduate entrepreneurs in the Business Administration Department of Semarang State Polytechnic must excel in, among other things, effective time management between their academic pursuits and business activities.